In-situ investigation of dynamic deformation in NiTi shape memory alloys under laser induced shock. (November 2017) - Wang, Xi; Xia, Weiguang; Wu, Xianqian; Wei, Yanpeng; Huang, Chenguang
Highlight: Photonic Doppler velocimetry (PDV) was used to track the free surface particle velocity of NiTi shape memory alloy during laser shock peening (LSP) to study the deformation behavior at ultrahigh strain rate. There exists a critical peak pressure between 4.5 GPa and 7.5 GPa for NiTi shape memory alloy to induce martensitic transformation during laser induced shock. The dynamic transition stress and the dynamic tensile strength of NiTi alloys at ultrahigh strain rate were determined from the experimentally measured surface velocity profile. Abstract: The free surface particle velocity of NiTi target shocked with a pulsed laser beam was measured with a photonic Doppler velocimetry (PDV) system to study the dynamic deformation behavior of NiTi alloys at ultra-high strain rate of 10 6 ∼10 7 /s. Through the analysis of the particle velocity profiles, the shock wave intensity was found to have the influence on the process of austenite-martensite transformation. Theoretical analysis of shock wave propagation showed that the first plateau in the velocity profile was caused by martensitic transformation and the second plateau if existing is caused by the subsequent plastic yielding of shock induced martensite. Residual martensite of the NiTi, which exhibited as needlelike structures, was observed in the laser shocked region. Based on the present results, and the studies by Nemat-Nasser et al. (2005), Liao et al. (2012), and Wang et al. (2013), we concluded that laser induced shock can cause the martensitic transformation as long as the laser induced shock pressure reaches a critical value. The dynamic transition stress and the dynamic tensile strength of NiTi alloys were also determined from the experimentally measured surface velocity profile.